STUDENTS’ DIFFICULTIES IN TRANSLATING NARRATIVE TEXT AT GRADE EIGHTH IN SMP SWASTA CINTA RAKYAT 2 PEMATANGSIANTAR - Ummi Kalsum Siahaan; Sanggam Siahaan; Bloner Sinurat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to analyze the difficulties faced by eighth-grade students at SMP Swasta Cinta Rakyat 2 Pematangsiantar in translating narrative texts from English into Bahasa Indonesia and to identify the strategies they use in the translation process. The study employed a descriptive qualitative method involving 17 students as participants. Data were collected through students’ translation tasks and analyzed based on Nida and Taber’s (1982) theory of translation difficulties and Mona Baker’s (1992) translation strategy framework. The findings reveal that students experienced linguistic difficulties particularly in vocabulary (100%), grammar (100%), and word choice (88.2%) while non-linguistic factors were not identified. Regarding translation strategies, students used six out of eight strategies proposed by Baker: translation by paraphrase using a related word (28.07%), omission (26.32%), paraphrase using an unrelated word (15.79%), more general word (14.04%), more neutral/less expressive word (12.28%), and loan word plus explanation (3.51%). The dominant strategy, translation by paraphrase using a related word, indicates students’ attempts to maintain meaning despite limited vocabulary mastery. The study concludes that insufficient linguistic competence, especially in vocabulary and grammar, remains the main obstacle in students’ translation performance.